I am trying to find the solution for $$x''=-2\beta x'-x+\gamma\cos(\omega t)$$ with $\beta,\gamma,\omega$ positive constants. I started by finding the homogeneous part of the solution by solving $x''+2\beta x'+x=0$ and found $$x_{hom}=c_1e^{\lambda_+ t}+c_2e^{\lambda_- t}$$ with $\lambda_{\pm}=-\beta\pm\sqrt{\beta^2-1}$. Now to find the particular solution I try to use the variation of constants, hence I need to solve the system $$c_1'(t)e^{\lambda_+ t}+c_2'(t)e^{\lambda_- t}=0\\ c_1'(t)\lambda_+ e^{\lambda_+ t}+c_2'(t)\lambda_- e^{\lambda_- t}=\gamma \cos(\omega t) $$ I did so and found: $$c_1=\frac{\gamma}{4\sqrt{\beta^2-1}(i\omega-\lambda_+)}e^{(i\omega-\lambda_+)t}-\frac{\gamma}{4\sqrt{\beta^2-1}(i\omega+\lambda_+)}e^{-(i\omega+\lambda_+)t}$$ and $$c_2=-\frac{\gamma}{4\sqrt{\beta^2-1}(i\omega-\lambda_-)}e^{(i\omega-\lambda_-)t}+\frac{\gamma}{4\sqrt{\beta^2-1}(i\omega+\lambda_+)}e^{-(i\omega+\lambda_-)t}$$ Now the particular solution is $$x_p=c_1e^{\lambda_+ t}+c_2e^{\lambda_- t}$$

However in my course the particular solution was given to be $$x_p=a \cos(\omega t) + b \sin(\omega t)$$ with $$a=\frac{(1-\omega^2)\gamma}{(1-\omega^2)^2+4\beta^2\omega^2}, b=\frac{-2\beta\omega\gamma}{(1-\omega^2)^2+4\beta^2\omega^2}$$ and I just can't connect my result to this one! Where is my error?

  • $\begingroup$ May be, you need to get rid of the imaginaty part in denominator. $\endgroup$ – Claude Leibovici Dec 14 '15 at 13:46

The method of "variation of parameters" (which is very usefull in case of first order non-homogeneous linear ODE) is rather booring in case of second order - . Of course, it is of use if no simpler approach can be found.

In the present case, obviously a particular solution will fit of the form : $$x_p=a \cos(\omega t)+b \sin(\omega t)$$ that we bring back into the ODE : $$-a\omega^2 \cos(\omega t)-b\omega^2 \sin(\omega t)=$$ $$=-2\beta\omega\left(-a \sin(\omega t)+b \cos(\omega t) \right) -a \cos(\omega t)-b \sin(\omega t)+\gamma\cos(\omega t)$$ Then, solve for $a$ and $b$ : $$-a\omega^2 =-2\beta\omega b -a +\gamma $$

$$-b\omega^2 =2\beta\omega a -b $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.